The regent's involvement with the village of peduli TBC (tuberculosis) - Widiastuti, Yunita (BKM Public Health and Community Medicine, 2021)
TBC is still a serious problem for the government to date. TBC services are still widely available in urban areas, making it difficult for some people in rural areas to access services. Village-based TB services, if any, are still not optimal for prevention, even if they exist, they are only perfunctory. TB Care Village is expected to be able to accelerate the prevention and control of TB. The service program TB Care Village can be reached by all people, especially TB sufferers, which include : TB sufferers obey medical services, provision of additional TB nutrition and Rewards Service providers face the population directly. A public health service officer called P2M is assisted by a female health cadre, are recruited from local residents who understand the local culture.